Effects of Clinoptilolite on the Digestibility of Nutrients and Relative Organ Weights in Rat Diets - Aydın Ketani; Ramazan Demirel; Murat Sedat Baran; Dilek Şentürk Demirel; Beran Yokuş (Journal of Agricultural Sciences)
This study was conducted to compare the effects of dietary clinoptilolite on nutrient digestibility and relative organweights in rats. In this study, 24 adult male Sprague-Dawley rats were divided into 4 groups with 3 replicates, accordingto a randomized split plots design. In addition to a control group (0% clinoptilolit), 3 levels of clinoptilolite (2%, 4%, and6%) were used in the diets, and the rats were fed (individually in cages) these diets for 56 days. Statistically significantdifferences were found among the groups for the digestibility rates of nutrients (P<0.05), except for crude fibre (CF) andacid detergent fibre (ADF). The addition of clinoptilolite in rats’ feeds reduced the digestibility of crude fibre, crude ash(CA), neutral detergent fibre (NDF) and acid detergent fibre (ADF), but increased the digestibility of other nutrients.Slaughter live, organs (liver, kidney, heart, and stomach) and relative organ weights were not affected significantly by theclinoptilolite contents (P>0.05). In conclusion, clinoptilolites can be used in animal feed as natural toxin binders whenstored under suitable conditions.